Răspunsuri

2014-08-26T20:30:01+03:00
X = primul numar
y = al 2-lea numar
z = al 3-lea numar
----------------------
x = 3y / 4
x + 40 = z
(x + y + z)/3 = 80
-------------------
4x - 3y               = 0
  x          - z        = -40 
  x + y   + z        = 240
------------------  adunam ecuatia a 2-a cu ecuatia a 3-a si scapam de z
4x - 3y               = 0
2x + y     /         = 200  l * 3
----------------------------------
4x - 3y               = 0
6x+ 3y               = 600
-------------------------------------- Adunam ecuatiile si scapam de y
10x  /                 = 600

=> x = 600 / 10 = 60

x = 3y/4
=>y = 4x/3 = 4 * 60 / 3 = 4 * 20 = 80

z = x+40 = 60 + 40 = 100


 


2 4 2